Artificial Intelligence and its Applications from a Financial and Monetary Perspective - Iraq a Case Study - Mohammed Medlool Ali Al-Sultani; Hiba Saad Abdul Jabbar; Nooraldeen Sabah Mahdi Kamalaldeen (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Artificial intelligence has emerged as a transformative technology of the Fourth Industrial Revolution and has increasingly become integrated into economic, financial, and monetary activities worldwide. Specific Background: Financial institutions are adopting artificial intelligence to improve operational efficiency, support decision-making, strengthen fraud detection, enhance customer services, and facilitate financial management processes. Knowledge Gap: Despite the growing adoption of artificial intelligence in financial systems, limited studies have comprehensively examined its financial and monetary applications within the Iraqi context and its potential contribution to public financial management. Aims: This study aims to examine the concept of artificial intelligence, identify its major applications in financial and monetary activities, and explore its role in supporting financial development in Iraq. Results: The study found that artificial intelligence contributes to risk assessment, fraud detection, anti-money laundering activities, customer service, investment management, financial planning, and public financial administration. Statistical indicators also show substantial growth in digital financial infrastructure in Iraq, including automated teller machines, point-of-sale devices, electronic cards, bank accounts, and digital wallets between 2017 and 2024. Novelty: The study combines theoretical and practical perspectives by linking artificial intelligence applications with monetary and financial developments in Iraq. Implications: The findings highlight the growing importance of artificial intelligence in improving financial performance, supporting financial governance, strengthening digital transformation, and facilitating efficient monetary and financial operations. Keywords: Artificial Intelligence, Financial Systems, Monetary Systems, Digital Banking, Financial Technology Key Findings Highlights Electronic financial infrastructure recorded substantial growth during the study period. Intelligent technologies support fraud prevention and regulatory compliance activities. Advanced computational models facilitate auditing and public resource management.